Connections between family violence and violence in the public sphere in Afghanistan - Mina Orang; Fiona Choi; R. Michael Krausz; Atal Hewad; Janet Suen; Kerry Jang; Inge Missmahl (Humanities & Social Sciences Communications, 2023)
Abstract Afghanistan has endured over four decades of violence in the public sphere, such as war and suicide attacks. To effectively provide psychosocial counseling using a psychodynamic approach in Afghanistan, it is crucial to recognize the potential connection between ongoing public violence and high rates of family violence. In 2019, we conducted a study to explore the relationship between public violence and family violence among Kabul residents, including those seeking counseling and those who were not. Our cross-sectional mixed methods survey recruited 299 participants from a psychosocial counseling service as well as community members who were not receiving the service. The findings revealed a significant positive correlation between experiences of public violence and family violence. Both clients and non-clients reported experiencing high levels of violence, which led to impairments in daily functioning and increased suicidality. Additionally, a thematic analysis of open-ended questions indicated changes in attitudes resulting from exposure to violence, including feelings of helplessness and hopelessness both in and out of the home. We conclude that applying a psychodynamic approach to psychosocial counseling in Afghanistan requires awareness of the positive correlation between public violence and family violence in a society that has been exposed to violence in the public sphere for over forty years. Mental health care needs to contribute towards breaking cycles of violence by empowering clients to take control of their lives and become agents of change within their families and communities.